UPAYA MENINGKATAN SIKAP BELAJAR SEJARAH DENGAN MODEL THINK PAIR SHARE KELAS X P.IPS 3 SMA NEGERI 2 KABANJAHE - Agustina Banjarnahor (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Abstract: Efforts Improving Attitudes Learning History With Model Think Pair Share Class X SMAN 2 P.IPS 3 Kabanjahe. This research was conducted at SMAN 2 Kabanjahe located at Jln. Jamin Ginting Kabanjahe. Subjects were students of class X-3 SMA Negeri 2 P.IPS Kabanjahe in the school year 2015/2016 totaling 31 students. History learning outcomes of students in the subject matter and Cross-Cultural Islamization in the archipelago by applying the learning model TPS increases. Early tests of student learning outcomes is not a complete study, the average value of 29. The results of the study showed students completed the first cycle of 23 students, the percentage of completeness 74%, the average value of grade 74.2. Cycle II students completed a total of 27 people, the percentage of classical completeness 87%, the value of the average grade of 84.5. Keywords: Model Learning Think-Pair-Share, Attitude Learning, Learning Outcomes   Abstrak : Upaya Meningkatan Sikap Belajar Sejarah Dengan Model Think Pair Share Kelas X P.IPS 3 SMA Negeri 2 Kabanjahe. Penelitian ini dilakukan di SMA Negeri 2 Kabanjahe yang bertempat di Jln. Jamin Ginting Kabanjahe. Subyek penelitian adalah siswa-siswi kelas X-P.IPS 3 SMA Negeri 2 Kabanjahe Tahun Pelajaran 2015/2016 yang berjumlah 31 siswa. Hasil belajar Sejarah siswa pada materi pokok Islamisasi dan Silang Budaya di Nusantara dengan menerapkan model pembelajaran TPS meningkat. Awal tes hasil belajar siswa tidak seorang tuntas belajar, nilai rata-rata 29. Hasil belajar pada siklus I menunjukan siswa tuntas 23 orang siswa, persentase ketuntasan 74%, nilai rata-rata kelas 74,2. Siklus ke II siswa tuntas sebanyak 27 orang, persentase ketuntasan klasikal 87%, nilai rata-rata kelas 84,5.   Kata Kunci:  Model Pembelajaran Think-Pair-Share, Sikap Belajar, Hasil Belajar